Even lobar deposition of poorly soluble gold nanoparticles (AuNPs) is similar to that of soluble silver nanoparticles (AgNPs) - Hoi Pin Kim; Jin Kwon Kim; Mi Seong Jo; Jung Duck Park; Kangho Ahn; Mary Gulumian; Günter Oberdörster; Il Je Yu (Particle and Fibre Toxicology, 2020)
Abstract Background Information on particle deposition, retention, and clearance is important when evaluating the risk of inhaled nanomaterials to human health. The revised Organization Economic Cooperation and Development (OECD) inhalation toxicity test guidelines now require lung burden measurements of nanomaterials after rodent subacute and sub-chronic inhalation exposure (OECD 412, OECD 413) to inform on lung clearance behavior and translocation after exposure and during post-exposure observation (PEO). Lung burden measurements are particularly relevant when the testing chemical is a solid poorly soluble nanomaterial. Previously, the current authors showed that total retained lung burden of inhaled soluble silver nanoparticles (AgNPs) could be effectively measured using any individual lung lobe. Methods and results Accordingly, the current study investigated the evenness of deposition/retention of poorly soluble gold nanoparticles (AuNPs) after 1 and 5 days of inhalation exposure. Rats were exposed nose-only for 1 or 5 days (6 h/day) to an aerosol of 11 nm well-dispersed AuNPs. Thereafter, the five lung lobes were separated and the gold concentrations measured using an inductively coupled plasma-mass spectrophotometer (ICP-MS). The results showed no statistically significant difference in the AuNP deposition/retention among the different lung lobes in terms of the gold mass per gram of lung tissue. Conclusions Thus, it would seem that any rat lung lobe can be used for the lung burden analysis after short or long-term NP inhalation, while the other lobes can be used for collecting and analyzing the bronchoalveolar lavage fluid (BALF) and for the histopathological analysis. Therefore, combining the lung burden measurement, histopathological tissue preparation, and BALF assay from one rat can minimize the number of animals used and maximize the number of endpoints measured.